PENTINGNYA MEMAHAMI SIKAP TERHADAP MEMBACA PADA SISWA DALAM PEMBELAJARAN BAHASA - Umam, Aguswan Khotibul (English Education: Jurnal Tadris Bahasa Inggris, 2013)
Positive and favorable behaviour towards reading can encourage students to read. Having a lot of reading activities can enhance reading ability. The students who enjoy readingwill be more often doing reading activity. The activity can promote knowledge and experiences in reading texts that eventually it can increase reading comprehension. Teacher role in the process of establishing positive behaviour towards reading is needed to create joyful circumstances and internalizing the value of reading advantages. If the students have reading skills and find it is convenient to read, they will have more possitive behaviour towards reading. This condition can boost students’ reading ability And comprehension.